Incidence and severity of coronary artery disease in patients with atrial fibrillation undergoing first-time coronary angiography. - Stefan Kralev; Kathrin Schneider; Siegfried Lang; Tim Süselbeck; Martin Borggrefe (PLoS ONE)
Background In standard reference sources, the incidence of coronary artery disease (CAD) in patients with atrial fibrillation (AF) ranged between 24 and 46.5%. Since then, the incidence of cardiovascular risk factors (CRF) has increased and modern treatment strategies ("pill in the pocket") are only applicable to patients without structural heart disease. The aim of this study was to investigate the incidence and severity of CAD in patients with AF. Methods From January 2005 until December 2009, we included 261 consecutive patients admitted to hospital with paroxysmal, persistent or permanent AF in this prospective study. All patients underwent coronary angiography and the Framingham risk score (FRS) was calculated. Patients with previously diagnosed or previously excluded CAD were excluded. Results The overall incidence of CAD in patients presenting with AF was 34%; in patients >70 years, the incidence of CAD was 41%. The incidence of patients undergoing a percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) was 21%. Patients with CAD were older (73±8 years vs 68±10 years, p = 0.001), had significantly more frequent hypercholesterolemia (60% vs 30%, p<0.001), were more frequent smokers (26% vs 13%, p = 0.017) and suffered from angina more often (37% vs 2%, p<0.001). There was a significant linear trend among the FRS categories in percentage and the prevalence of CAD and PCI/CABG (p<0.0001). Conclusions The overall incidence of CAD in patients presenting with AF was relatively high at 34%; the incidence of PCI/CABG was 21%. Based upon increasing CRF in the western world, we recommend a careful investigation respecting the FRS to either definitely exclude or establish an early diagnosis of CAD--which could contribute to an early and safe therapeutic strategy considering type Ic antiarrhythmics and oral anticoagulation.